The Krzyzewskiville Tales - Dinin, Aaron, 1983- (Book collections on Project MUSE., 2005)
Recent Duke University graduate Aaron Dinin has produced an entertaining, imaginative look at Krzyzewskiville, the tent city named after Duke University's head men's basketball coach Mike Krzyzewski (Sha-shef-ski). A unique Duke tradition, Krzyzewskiville is used to determine which students are admitted into key games. Taking Geoffrey Chaucer's Canterbury Tales as his model, Dinin has created characters who narrate their semifictionalized tales--by turns reverent, bawdy, and humorous--to enlighten readers about this cherished institution.So the story begins. On a wintry night in Durham, North Carolina, writes Dinin, twelve students huddle under the meager protection of a nylon tent. They have little in common except the sacrosanct tradition that has brought them together for the past month. Before the sun next sets, they will anoint themselves in blue and white paint and enter nearby Cameron Indoor Stadium to worship at the altar of Blue Devils basketball. In the meantime, they abide in Krzyzewskiville.A stranger enters the tent, a respected sportswriter, and suggests that the tenters pass the hours until the next tent check by telling stories of Krzyzewskiville. Like Chaucer's pilgrims, the students compete to tell the best tale. They report on ribald tenting exploits, relate a dream in which Duke basketball players and coaches test a fan's loyalty, debate the rationality of tenting as a way of allocating students' tickets, and describe the spontaneous tent city that sprang up one summer when their beloved "Coach K" was offered a job elsewhere. This storytelling competition creates a loving portrait of the complex rules and tribal customs that make up the rich community and loyal fans that are Krzyzewskiville.Mickie Krzyzewski, Coach K's wife and a familiar courtside figure at Duke basketball games, has contributed a foreword praising the "love, commitment, and ownership" of the citizens of Krzyzewskiville.